Alteplase or tenecteplase for thrombolysis in ischemic stroke: An illustrated review. Issue 6 (20th September 2022) - Zhu, Annie; Rajendram, Phavalan; Tseng, Eric; Coutts, Shelagh B.; Yu, Amy Y. X.
Abstract: Intravenous thrombolysis is a standard of care treatment for patients with acute ischemic stroke. Tissue plasminogen activator (tPA) has been the main thrombolytic agent used since the publication of the seminal National Institutes of Neurological Disorders and Stroke trial in 1995. There is now mounting evidence to support the routine use of Tenecteplase (TNK) to treat acute ischemic stroke. TNK is a genetically modified tPA with higher fibrin specificity, longer half‐life, and reduced systemic coagulopathy. In this illustrated review, we compare the indications, doses, mechanisms of action, efficacy and safety of TNK and tPA. We provide an overview of published clinical trials studying TNK in acute ischemic stroke, including dose‐escalation studies and head‐to‐head comparisons with tPA. Finally, we summarize current acute stroke guideline recommendations and suggest treatment algorithms to manage the two main complications of intravenous thrombolysis: symptomatic intracerebral hemorrhage and angioedema.